PENINGKATAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PROTEIN HEWANI MELALUI MEDIA AUDIO-VISUAL SEBAGAI UPAYA PENCEGAHAN STUNTING - Andesti; Rohani; Yuanita, Vera (Jurnal Kesehatan dan Pembangunan, 2025)
According to World Health Organization (WHO) data in 2020, Indonesia is the second highest in Southeast Asia at 31.8%, (Ashilah et al. 2023). The purpose of the research is to know the increase in knowledge and attitudes of pregnant women about animal protein through audio-visual media as an effort to prevent stunting. This study uses a quasi-experimental research design with a pretest-posttest control group design approach. Based on the results of the study, it is known that the average knowledge of mothers before being given audio-visual media is 49.33 and the average knowledge of mothers after being given audiovisual media education on animal protein has increased to 49.48. So it can be concluded that audio-visual media has an effect in improving the mother's attitude in preventing stunting obtained a significant value of 49.53 which is smaller than the significant level of 5% or (p value 0.000 0.05), then it can be stated that there is an influence of audio-visual media on the attitude of mothers in preventing stunting at PMB Ferawati SST Palembang in 2024. It is hoped that this research can be further refined by conducting similar research using more samples, using different methods and using other interventions such as using leaflets, booklets or using whattsapp media so that research on the provision of Audio Visual Media as an Effort to Prevent Stunting can be even better